Eurípides, Hercules, ed. K. H. Lee, Leipzig, Teubner Verlagsgesellschafts, 1988, XVIII + 59 pp. (Minerva. Revista de Filología Clásica, 2019)
Reseña de Eurípides, Hercules, ed. K. H. Lee, Leipzig, Teubner Verlagsgesellschafts, 1988, XVIII + 59 pp.